Ação rescisória com fundamento na violação de súmula vinculante e persuasiva - Gomes, Thais Matallo Cordeiro (2014)
This dissertation has as its aim the study of the possibility of filing an action for the reversal of res judicata based on a Brazilian Superior Court of Justice (STJ) precedent, which may be binding or merely persuasive. The current position of the STJ is in the sense that precedents are not equivalent to legal statutes and, therefore, may not serve as grounds for the action to reverse res judicata, based on article 485, V, of the Brazilian Procedural Law Code (CPC). This paper analyses the aforementioned court position, in order to reach a conclusion (de lege lata) on whether there are grounds for an action to reverse res judicata based on the violation of a binding and/or persuasive precedents. For this purpose, the author opted to initiate the dissertation with a brief study of the main features of the action to reverse res judicata. Emphasis will be given to article 485, V, of CPC, specially to the definition and interpretation of the said "literal violation of the Law" (among others). Subsequently, the precedents (binding and persuasive) will be analysed. The author starts from general aspects towards polemical and practical questions related to the matter under study, e.g., the effects and reach of the precedents, as well as the possible and questionable interference of the Judiciary in the constitutional competence of the Legislature. At this time, the legal nature of the precedents and its possible equivalence to statutory law will be also evaluated under the light of the general law principles. Finally, as a result of the argumentative line developed on the previous chapters, the dissertation will state whether the Brazilian legal system allows an action to reverse res judicata based on binding and persuasive precedents. Procedural aspects of the action will be also tackled (e.g. time limitation and first day of the term to file the action). After the study, precisely on the basis of art. 485, inc. V, of the CPC code, the conclusion is by the possibility of filing a rescission action when observed violation of binding and persuasive precedents